2006
DOI: 10.1183/09031936.06.00055805
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COPD symptoms: does the sex of the patient matter?

Abstract: Although chronic obstructive pulmonary disease (COPD) patients frequently report symptoms, it is not known which factors determine the course of symptoms over time and if these differ according to the sex of the patient. The current study investigated predictors for presence, development and remission of COPD symptoms in 816 males and 312 females completing 3-yrfollow-up in the European Respiratory Society Study on Chronic Obstructive Pulmonary Disease (EUROSCOP).The following were included in generalised esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
4
26
1
Order By: Relevance
“…They may, therefore, be more likely to be classified as having an exacerbation. However, there are also data indicating that females are at higher risk of being hospitalised for exacerbations [37], which is unlikely to be due solely to differential symptom reporting. A higher MRC dyspnoea grade may identify patients more likely to receive exacerbation treatment when they present with worsening symptoms.…”
Section: Mortalitymentioning
confidence: 99%
“…They may, therefore, be more likely to be classified as having an exacerbation. However, there are also data indicating that females are at higher risk of being hospitalised for exacerbations [37], which is unlikely to be due solely to differential symptom reporting. A higher MRC dyspnoea grade may identify patients more likely to receive exacerbation treatment when they present with worsening symptoms.…”
Section: Mortalitymentioning
confidence: 99%
“…17 In developing countries where biomass fuels are used to heat homes and cook meals, women develop COPD more frequently from indoor air pollution than from cigarette exposure. 15,[18][19][20][21] Exposure to biomass fuels, occupational exposures, and remodelled asthma are important causal agents in the estimated 15% of individuals with COPD who have never smoked. 22,23 Differences in lung growth rates between males and females combined with early age of smoking initiation 24,25 and sex-specific smoking behaviours 26,27 further enhance the susceptibility of women to tobacco smoke.…”
Section: Susceptibilitymentioning
confidence: 99%
“…The EUROSCOPE study 106 , which included 816 men and 312 women with COPD, showed that respiratory symptoms (wheeze, dyspnoea, cough and phlegm) were associated with lung function in men only. Another populationbased study found that women with or without COPD reported similar health status, whereas men with COPD reported significantly worse health status than men without COPD 139 .…”
Section: Factors Associated With Low Physical Activitymentioning
confidence: 99%